Nutraceuticals and skin appearance: Is there any evidence to support this growing trend?. Issue 1 (13th February 2018) - Spiro, A.; Lockyer, S.
Abstract: The rise of the nutraceutical market, specifically oral nutrition supplements claiming to improve skin appearance, is striking. This paper aims to examine the published scientific evidence for beneficial effects of nutraceuticals on skin appearance. An overview of skin physiology and intrinsic and extrinsic ageing is provided which underlies the potential physiological processes nutraceuticals purport to counter. Common ingredients used are explored. Some of these (vitamins A, C, B2, B3, B7, copper, iodine, zinc) have authorised skin‐related health claims, but many do not. Current evidence for those without existing authorised claims ( e.g . green tea extract, pomegranate extract, carotenoids, evening primrose oil, borage oil, fish oil, collagen and co‐enzyme Q10) is reviewed, focussing primarily on evidence from randomised controlled trials where available, in relation to skin parameters including wrinkles and hydration. Issues of safety are also considered, and the postulated mechanisms for some emerging ingredients, such as cocoa flavanols and probiotics, are explored. Evidence from high quality human trials demonstrating clear benefit is required by regulatory authorities in order for foods and nutrition supplements to carry a health or beauty claim. To date, the evidence for many ingredients in relation to skin appearance is limited, not sufficiently robust and/or inconsistent. Although there are a small number of human studies suggesting a potential benefit and some plausible biological mechanisms, much of the evidence to date comes from animal and in vitro studies. There are simply not enough good quality randomised controlled trials in this area to draw firm conclusions about the benefit of nutraceuticals to skin appearance.